A Dual Atrioventricular Approach to Repair Pseudoaneurysm after Mitral Valve Surgery - Fishberger, Gregory; Bulard, Blake; Lozonschi, Lucian (The Thoracic and Cardiovascular Surgeon Reports, 2023)
Background Left ventricular pseudoaneurysm (LVPA) is an uncommon but potentially fatal complication following atrioventricular groove rupture.Case Description We present a patient with a massive LVPA involving the lateral commissure and under the mitral P3 segment following coronary artery bypass grafting and mitral valve (MV) repair. MV replacement and arteriovenous pseudoaneurysm were repaired by dual approach via the left atrium with excision of the previously dehisced mitral ring to expose the defect and patch repair the atrioventricular defect through the pseudoaneurysm free wall.Conclusion This is a rare case of a large subacute postoperative LVPA repaired by dual atrial–ventricular approach to treat a contained atrioventricular groove rupture.
Keywords: aneurysm; coronary artery bypass grafting; CABG; heart; mitral valve surgery; surgery; complications